The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/asj.13344
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of supplementation with β‐carotene on the growth performance and intestinal mucosal barriers in layer‐type cockerels

Abstract: Development of automatic breeding management accelerated the growth of chicks. However, health conditions of the chicks become more susceptible to external antigens. Mortality of neonates is closely related to the economic profit; thus, maintaining the fitness of young poult is the primary mission. The early growth and development of the intestine in the poults is a crucial process related to the fitness of the chicks. Gut barriers form a key line of defense against the foreign antigens of the environment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Interestingly, dietary supplementation with 12,000 IU/kg VA could alleviate the upregulation of ZO-1 and claudin-1 with CCP challenge. In addition, the mRNA level of mucin-2 was upregulated with VA addition, which is consistent with another study [ 15 ]. Mucin-2 secreted by goblet cells adheres to the surface of the intestinal villi and is considered the first physical barrier of the intestine [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, dietary supplementation with 12,000 IU/kg VA could alleviate the upregulation of ZO-1 and claudin-1 with CCP challenge. In addition, the mRNA level of mucin-2 was upregulated with VA addition, which is consistent with another study [ 15 ]. Mucin-2 secreted by goblet cells adheres to the surface of the intestinal villi and is considered the first physical barrier of the intestine [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…Another study demonstrated that VA has the ability to maintain the integrity of the epithelium and mucosa [ 14 ]. Additionally, some studies suggested that a lack of VA in the diet might provide an opportunity for NE and other intestinal diseases in broilers [ 11 , 15 ]. At present, the effects of VA on NE in broilers have not been fully characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation is closely related to intestinal barrier function (38), bcarotene is mainly absorbed in the intestine, it has affinity with intestinal epithelial cells, enters the cytoplasm through the brush edge membrane, and then plays role after being catalyzed by enzymes (39). b-carotene robusts modulator of mucosal barriers (40), it improves villus height and villus height to crypt depth ratio and microbiota composition in this study, which has positive effect on the barrier function.…”
Section: Discussionmentioning
confidence: 51%
“…Anacardium occidentale L. contains various nutrients and bioactive compounds, including monounsaturated fatty acids, β-carotene, lutein, zeaxanthin, vitamin E as tocopherols, dietary fibers, flavonoids, catechins, amino acids, minerals, anacardic acids, cardanols, cardols, and phytosterols [ 21 , 24 , 25 ]. Most of these bioactive compounds present in cashew nuts play an important role in gut health as demonstrated by studies; catechins can modulate microbiota [ 26 ], selenium can affect gut microbial colonization avoiding health damage associated with dysbiosis [ 27 ], β-carotene can increase tight junctions expression (ZO-1, ZO-2, occludin), MUC-2 and MUC-3 expression, and increase villus height and villi height/crypt depth ratio [ 28 , 29 ], and lutein can decrease crypt depth [ 30 ]. Furthermore, flavonoids can modulate biomarkers relevant to intestinal inflammation [ 31 ].…”
Section: Introductionmentioning
confidence: 99%